2016
DOI: 10.5935/0103-5053.20160069
|View full text |Cite
|
Sign up to set email alerts
|

A Study of the Interaction Betweentrans-Dehydrocrotonin, a Bioactive Natural 19-nor-Clerodane, and Serum Albumin

Abstract: The interaction between 19-nor-clerodane trans-dehydrocrotonin (from Croton cajucara Benth.) and bovine serum albumin was studied, applying spectroscopic techniques (fluorescence and circular dichroism), combined with molecular modeling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…34 Table 1 shows that ΔH° and ΔS° values are negative and positive, respectively, for HSA:BZL, HSA:MTZ and HSA:MZ, indicating hydrogen bonding and electrostatic forces as the main binding forces in the binding process. 35 While for HSA:NFX interaction, hydrogen bonding and hydrophobic interaction are the main binding forces. 33 From the standpoint of water structure, positive entropy is often regarded as a typical signature of hydrophobic interaction, since the water molecules which are arranged in an orderly fashion around the ligand and the protein molecules acquire a more random configuration as a result of hydrophobic interactions.…”
Section: Resultsmentioning
confidence: 99%
“…34 Table 1 shows that ΔH° and ΔS° values are negative and positive, respectively, for HSA:BZL, HSA:MTZ and HSA:MZ, indicating hydrogen bonding and electrostatic forces as the main binding forces in the binding process. 35 While for HSA:NFX interaction, hydrogen bonding and hydrophobic interaction are the main binding forces. 33 From the standpoint of water structure, positive entropy is often regarded as a typical signature of hydrophobic interaction, since the water molecules which are arranged in an orderly fashion around the ligand and the protein molecules acquire a more random configuration as a result of hydrophobic interactions.…”
Section: Resultsmentioning
confidence: 99%
“…1.0 at 296, 303 and 310 K) indicate the existence of just one main binding site in the BSA structure for PIA. 30 Basically, four main types of interaction (hydrogen bond, electrostatic, van der Waals and hydrophobic forces) play critical roles in the association between small molecules and macromolecules. In order to characterize the forces between PIA and BSA, thermodynamic parameters were calculated using the van't Hoff equation (5) where, ΔH°, ΔS°, ΔG° are the enthalpy, entropy and Gibbs free energy change, respectively; R is the gas constant (R = 8.314 × 10 -3 kJ mol -1 K -1 ), T is the temperature (296, 303 and 310 K) and K b the binding constant.…”
Section: Fluorescence Quenching Studiesmentioning
confidence: 99%
“…phenylbutazone, azapropazone, tolbutamide, bucolome and sulfisoxazole), whose structural characteristics are similar to those in the PIA structure. 30,42 Figure 7A represents the molecular surface of BSA for the PIA pose with the best docking score. This figure shows that the major part of the PIA structure is accommodated inside the protein binding site, which could be related to the high binding constants values obtained in the fluorescence quenching experiments.…”
Section: Molecular Dockingmentioning
confidence: 99%
“…In vitro studies have shown that t-DCTN presents potential effects as antigenotoxic, 6 antileishmanial, 7 antiulcerogenic, 8 antitumor, [9][10][11] and hypoglycemic. 12 Recent publication from our group 13 on the interaction between t-DCTN and bovine serum albumin (BSA) demonstrated that there is a spontaneous, weak and entropy-driven association between BSA and t-DCTN in the ground state, typical of hydrophobic interactions. There is just one main binding site in serum albumin for t-DCTN causing a moderate change in the α-helix content of the albumin.…”
Section: Introductionmentioning
confidence: 99%
“…There is just one main binding site in serum albumin for t-DCTN causing a moderate change in the α-helix content of the albumin. 13 Recently, five semi-synthetic clerodanes based on the t-DCTN structure were synthesized and assayed against Ehrlich carcinoma and K562 human leukemia cells. Two of them showed remarkable biological activity: methyl-hydrazone (MHDCTN, Figure 1) and phenylhydrazone derivative (PHDCTN, Figure 1) 14 Since the binding ability HSA:drug is one of the steps for a possible pharmacological application and considering that MHDCTN and PHDCTN showed potential anti-cancer activity, the aim of the present study is the continuation of investigation of pharmacological aspects through their interaction with HSA.…”
Section: Introductionmentioning
confidence: 99%